Advances in non-invasive brain stimulation: enhancing sports performance function and insights into exercise science - Shuo Qi; Jinglun Yu; Li Li; Chen Dong; Zhe Ji; Lei Cao; Zhen Wei; Zhiqiang Liang (Frontiers in Human Neuroscience)
The cerebral cortex, as the pinnacle of human complexity, poses formidable challenges to contemporary neuroscience. Recent advancements in non-invasive brain stimulation have been pivotal in enhancing human locomotor functions, a burgeoning area of interest in exercise science. Techniques such as transcranial direct current stimulation, transcranial alternating current stimulation, transcranial random noise stimulation, and transcranial magnetic stimulation are widely recognized for their neuromodulator capabilities. Despite their broad applications, these methods are not without limitations, notably in spatial and temporal resolution and their inability to target deep brain structures effectively. The advent of innovative non-invasive brain stimulation modalities, including transcranial focused ultrasound stimulation and temporal interference stimulation technology, heralds a new era in neuromodulation. These approaches offer superior spatial and temporal precision, promising to elevate athletic performance, accelerate sport science research, and enhance recovery from sports-related injuries and neurological conditions. This comprehensive review delves into the principles, applications, and future prospects of non-invasive brain stimulation in the realm of exercise science. By elucidating the mechanisms of action and potential benefits, this study aims to arm researchers with the tools necessary to modulate targeted brain regions, thereby deepening our understanding of the intricate interplay between brain function and human behavior.